Engineering Characteristics and Stabilization Performance of Aggregate Quarry By-Products From Different Sources and Crushing Stages - Hou, Wenting; Qamhia, Issam; Mwumvaneza, Vincent; Tutumluer, Erol; Ozer, Hasan (Frontiers in Built Environment, 2019)
Quarry by-products (QB), usually less than 1/4 in. (6 mm) in size, are the residual deposits from the production of required grades of aggregate. This paper provides findings of a detailed laboratory study with the objective of characterizing the engineering properties of QB materials produced in the primary, secondary, and tertiary aggregate production stages from four different quarries operating in Illinois. Property tests were conducted for determining aggregate gradation, morphological shape characteristics, compaction properties (moisture-density), chemical composition and strength properties of QB samples. Since the unconfined compressive strength for QB materials is relatively low, chemical admixture stabilizers such as Portland cement and Class C fly ash were used to improve the strength properties. This study aims at evaluating properties governing the untreated and stabilized strength of QBs such as source variation, compacted density, chemical composition, gradation, particle shape and angularity, as well as the uniformity of distribution and the effectiveness of stabilizer. QB samples treated with 2% cement or 10% Class C fly ash by dry weight were found to be 10 to 30 times stronger than the virgin QB samples. Such significant increases in the strength of stabilized QB materials observed may indicate suitability of QBs for sustainable pavement applications.